Preparing Future Muslim Educators: Integrating Twenty-First Century Skills into Islamic Teacher Education Programs - Mukhlis Mukhlis (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2024)
This study aims to formulate an integrative framework for preparing future Muslim educators through the incorporation of twenty-first century competencies into Islamic teacher education. Using qualitative library research, the study reviews scholarly literature concerning teacher education, Islamic pedagogy, educational leadership, and competency-based learning. The analysis indicates that future Islamic educators require a combination of pedagogical expertise, digital literacy, critical thinking, creativity, communication, collaboration, and ethical leadership. The findings further suggest that teacher preparation programs should integrate Islamic values with contemporary educational competencies to produce adaptive and professionally competent educators capable of responding to educational transformation. The proposed framework combines competency-based education with Prophetic educational values to strengthen teacher professionalism and educational innovation. The novelty of this study lies in constructing a holistic competency model specifically designed for Islamic teacher education within the context of global educational transformation.